Analisa Visualisasi Data Akademik Menggunakan Tableau Big Data - Dedy Hartama (STIKOM Tunas Bangsa Pematangsiantar, 2018)
This research explains the benefits of data analysis by visualizing Big data in performing optimization in the academic management environment. The data used is academic information system database that related with student status. In this study the authors use Tableau tools to perform data analysis based on the number of students worksheet, student status, student name table and generate student dashboard data. The results of the analysis obtained by using visualization in bemtuk management graph is very fast and optimize data processing so mengatahui the development of academic database situation.